Outcome of Pantalar Fusion With Femoral Head Allograft in Avascular Necrosis of Talus - Ramu, Thiru Karthikeyan; Bajuri, Mohd Yazid; Hayyun, Muhammad Fathi; Mazli, Norliyana (Frontiers in Surgery, 2021)
Background: Avascular necrosis of the talus is a challenging condition which is caused primarily by trauma. The severity of the talus fracture determines the risk of avascular necrosis. Severe osteonecrosis with loss of talar integrity can be treated with arthrodesis and structural bone graft. Method: This study shows the experience of pantalar arthrodesis using hindfoot arthrodesis nail, screw fixation and femoral head allograft in four patients. Result: All patients were satisfied in terms of pain and function after an average of four months post-surgery. Limb length discrepancy was less than 1cm and hindfoot fusion was achieved by three months. The mean score for SF-36 physical function and AOFAS hindfoot score at two-year post pantalar arthrodesis was 88 and 80.8 respectively. Conclusion: Hindfoot ankle arthrodesis with usage of femoral head allograft can be successfully used for treatment of traumatic avascular necrosis of talus.